The COVID-19 Pandemic and Corporate Dividend Policy - Cejnek, Georg; Randl, Otto; Zechner, Josef (Journal of Financial and Quantitative Analysis, 2021)
Abstract This article shows that, for major equity markets, the proportion of index values attributable to the first 5 years of dividends dropped substantially in the first quarter of 2020 and that this drop was not reversed by the end of the year. In the cross section, this breakdown of dividend smoothing due to COVID-19 was less severe for firms with higher operating cash flows and more positively coskewed stock returns, and it was more pronounced for those with higher leverage and in the financial sector. Heavy dividend cutters also experienced a substantial increase in exposure to systematic risk.